Assessment Self-Care of Patients’ Undergoing Hemodialysis with end Stage Renal Disease - Haider Mohammed Haloob AL-Abedi1, Zahraa Abdull Abbass Al- Khafajy2 , Ali J. Eidan3 , Dhafer Ameen J (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: this study designed to assess self-care of patients’ undergoing hemodialysis with end stage renal disease and to determine out association between self-care of patients with end stage renal disease and their socio-demographic characteristics. Descriptive cross-sectional design is adopted in the recent study to perform the early stated objects. Started the study from (October 1st, 2016 until May, 6th, 2017). A Non-Probability (Accidental Sample) of (61) ESRD patients, those who visit dialysis centers of Al-Sadder Medical City in Al-Najaf Al-Ashraf., are included in the study sample. Analyzed data by descriptive analysis contains (Frequencies & Percentages) and statistical figures (Pie Charts) and Pearson’s Correlation Coefficients. The outcome of the present study that the self-care activities are interdependent and there is a positive relationship between the patients’ self-care with their age, income and marital status. While there is a non-significant difference between self-care activities and their clinical data in all items except there number of admission to emergency is a high significant difference. The study concludes that most patients with ESRD need moderate assistance in performing in dietary, exercise and other activities.